Evaluation of clinical features of ischemic colitis: Comparison between young and elderly - Tohda, Gen; Higashi, Seiju; Sumiyoshi, Ken-Ichi; Sakumoto, Hitoshi; Kato, Chikako; Kane, Teruyuki (Digestive endoscopy, 2005)
Background: It has been thought that ischemic colitis is caused by vascular and intestinal factors. Although elderly patients with arteriosclerosis are more susceptible to ischemic colitis, many young patients suffering ischemic colitis are also reported. The present study aimed to clarify the relationship between arteriosclerosis and ischemic colitis, and to evaluate various risk factors for ischemic colitis. Methods: We compared the clinical features of patients with ischemic colitis (54 cases) and control patients without ischemic colitis (86 cases), all diagnosed by colonoscopy. Subjects were classified into a young group (60 cases) under 60 years of age, and an elderly group (80 cases) of over 60 years. The degree of arteriosclerosis was measured by pulse wave velocity (PWV) level, and the effects of vascular and intestinal factors in the development of ischemic colitis were evaluated using multivariate analytical models. Results: In the elderly group, the PWV level was significantly higher in ischemic colitis patients than in the controls. By analyzing with multivariate analytical models, a high level of PWV and underlying diseases related to arteriosclerosis were thought to be risk factors for ischemic colitis in the elderly group. In the young group, intestinal factors such as irregular bowel movement, which is often seen in irritable bowel syndrome, habitual constipation, and prior history of an abdominal operation, were thought to be contributors to ischemic colitis. Conclusion: These findings suggest that intestinal factors in younger patients and vascular factors in more elderly patients are the primary contributors in the development of ischemic colitis.